(untitled) (Research, Society and Development, 2021)
Objective: To know the self-care of transsexual women in the light of Orem’s Self-Care Deficit Theory. Method: Study with 12 transsexual women from the Sexuality Outpatient Clinic of a University Hospital of Maranhão, Brazil. The Appraisal of Self-care Agency Scale (ASA-A) was used to assess the participants’ self-care ability. Results: More than half of the interviewees make adjustments to maintain health through situational changes (58,3%), make sure that the usual actions practiced to stay healthy are good (66.7%), report stimulus to perform their self-care (66,7%) and seek more current alternatives to take care of themselves (83,3%). Most women have good self-care capacity (66,7%). Conclusion: Knowing the meanings that transsexual women attribute to self-care is relevant due to the singularity in health and education that emerge from contact with diversity and identity.